The INFLUENCE OF SAFETY CULTURE ON SAFETY PERFORMANCE IN MARITIME SERVICE COMPANIES IN SURABAYA - Angga Maulana Putra; Ristanti Akseptori; R.A Norromadani Yuniati (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
Maritime service companies have a high risk of accidents due to the workplace environment at sea. To create a safe work environment, the company can implement a safety culture, which is assumed to be supported by workers' self-awareness to improve the company's Safety Performance. This study aimed to analyze the effect of Safety Culture on Safety Performance with moderation of Self Awareness. This study used purposive sampling with a sample size of one hundred and four organic employees who worked for at least one year at the company. This research uses a quantitative approach. The data collection technique used a questionnaire with a Likert scale. Validity and reliability tests were carried out to test the instrument. Hypothesis testing using multiple linear regression analysis methods and Moderated Regression Analysis (MRA) using SPSS version 22. The results showed that safety culture positively and significantly affects safety performance. Self-awareness does not have a positive and significant effect on safety performance and cannot moderate the effect of safety culture on safety performance on safety performance. This means that the better the implementation of the Safety Culture, the risk of work accidents in the company will decrease, so the company's Safety Performance will also increase.